Cyclic behavior and damage mechanism of 304 austenitic stainless steel under different control modes - YuanYuan Cui; WenTao Wang; Han Wang; Bin Li; Peng Zhao; FuZhen Xuan (Journal of Materials Research and Technology, 2024)
In this work, low cycle fatigue experiments under both strain and stress control modes with different loading levels were conducted on 304 austenitic stainless steel at ambient temperature to discuss the influence of loading mode and level on the cyclic response and physical mechanism. The results demonstrated that the cyclic response generally exhibited three stages: primary cyclic hardening, subsequent cyclic softening, and the secondary hardening finally. The degree of each hardening and softening stage was depended on not only the loading modes but also the strain/stress level. Accelerated cyclic softening and retarded secondary hardening occurred under the stress mode, which made a higher low-cycle fatigue life during stress cyclic loading than that for the strain control mode, especially at relatively high strain/stress level. The secondary hardening stage, occupying the main portion of the lifetime, was proved to be associated with the development of martensitic phase and the extension and intersecting of stacking faults or micro-twin.